Histological assessment of β‐amyloid precursor protein immunolabelled rectal biopsies aids diagnosis of equine grass sickness. (18th August 2017) - Jago, R. C.; Scholes, S.; Mair, T. S.; Pearson, G. R.; Pirie, R. S.; Handel, I.; Milne, E. M.; Coyle, F.; M gorum, B. C.
Summary: Background: An accurate, minimally invasive, ante‐mortem diagnostic test for equine grass sickness (EGS) is currently lacking. Although histological examination of haematoxylin and eosin‐stained rectal biopsies for chromatolytic neurons is insensitive as a diagnostic test for EGS, we hypothesised that its diagnostic accuracy could be improved by immunolabelling for β‐amyloid precursor protein (β‐APP), which has increased expression in cranial cervical ganglia (CCG) neuronal perikarya in EGS. Objectives: To develop a grading scheme for assessing the distribution and intensity of β‐APP immunoreactivity within individual rectal submucosal neurons and subsequently to determine the value of the distribution of different grades of neurons in EGS diagnosis. Study design: Retrospective case–control diagnostic accuracy study. Methods: Initially, a standardised grading scheme was developed and β‐APP immunoreactivity in individual neuronal perikarya and axons was compared in sections of CCG and ileum from EGS and control horses. The grading scheme was then refined before being blindly applied to submucosal neurons in rectal biopsies derived from 21 EGS and 23 control horses. Results: β‐APP immunoreactivity was increased in neuronal perikarya and axons in sections of CCG, ileum and rectum from EGS horses compared with controls. For rectal biopsies, a mean immunoreactivity grade exceeding 1.1 was 100% specific and sensitive for EGS, and the presence of at least one neuron with diffuse labelling of the entire cytoplasm (grade 3) was 95% sensitive and 100% specific for EGS. Main limitations: Although the diagnostic criteria facilitated the discrimination of the EGS and control biopsies evaluated in this study, further prospective validation using a larger sample set is required. Conclusions: Histological assessment of β‐APP immunolabelled rectal biopsies is more sensitive than conventional histological examination in EGS diagnosis. Further validation is required before this technique can be advocated for use in clinical decision making.